Meso-Forte - Innovative Method for Musical-Acoustic Psychotherapy and Neurohormonal Correction with Anti-Aging Effect: Clinical Study - Sergey V. Shushardzhan; Tatyana L. Allik; Natalya I. Eremina (Ministry of Health of the Russian Federation. National Medical Research Center of Rehabilitation and Balneology, 2022)
This article is devoted to Meso-Forte therapy (MFT) - the innovative scientific method of music therapy. In a long time of clinical studies, music therapy has identified various therapeutic and health-improving effects. Our team also studied regenerative possibilities of musical acoustic impacts on different cell cultures in vitro, including blood cells. Authors found an exciting phenomenon that specific acoustic parameters can intensify the activity of various cell cultures while others inhibit this activity. That data brought us to join healing factors in one technology. As a result, authors have developed MFT, which uses Digital algorithmic music therapy for stress-related mental disorders treatment and anti-aging; as well as local impacts of acoustic vibrations magnetic energy for skin rejuvenation. Aim. To learn the Meso-forte therapy effectiveness in treating stress-related neurosis with a concomitant skin disorder in the form of accelerated aging. Material and methods. The study involved 52 women aged 30 to 60 years with various signs of stress-related neurosis combined with accelerating face skin aging. All examined patients were randomly divided into two groups. The Leading group of 27 persons underwent MFT with the cosmetic masks: 10 procedures, 20-25 minutes each day. The Control group of 25 persons experienced listening to usual background music with the same cosmetic masks. The comprehensive research program included tests carried out before and after ten interventions. Psychological tests: WAM (Well-Being, Activity, Mood), Taylor's anxiety questionnaire. Medical tests: enzyme immunoassay method to measure cortisol and serotonin blood levels, laser doppler flowmetry to study blood flow in subcutaneous vessels, an objective device assessment of the skin condition. Results and discussion. In the Leading group, authors found reliable signs of mental-emotional improvement, optimization of the hormonal system, skin rejuvenation with the augmentation of the subcutaneous blood flow. In the Control group, there were no significant dynamics. Conclusion. Clinical study shows that MFT provides complex effects on the organism. Due to the integration of science, art, medicine, and modern technology, authors managed to create an effective high-tech tool for psychotherapy, healing, and rejuvenation that will be helpful to a doctor of any specialty or a psychologist.